Unlocking Access to Climate Finance for Pacific Island Countries - Fouad, Manal (Departmental Papers; Departmental Paper ;, 2021)
This departmental paper provides an in-depth overview of access to climate finance for Pacific Island Countries, evaluating successes and challenges faced by countries and proposes a way forward to unlock access to climate funds.